Repellent Activity Testing of an Essential Oil Gel Preparation of Cinnamon (Cinnamomun Burmanii) Bark) And Kaffir Lime Peel (Citrus Hytrix) Against Aedes Aegypti Mosquitoes - Fitriah Ardiawijianti Iriani; Rosita Irianti Dehi; Alpha Christyananda Damar (PT. Anagata Sembagi Education, 2024)
Dengue fever is still a disease that dominates, especially in the Papua region. To overcome this, it is necessary to modify preparations based on medicinal plants as mosquito repellents, one of which is gel preparations. This study aims to determine the repellent activity test of essential oil gel preparations of Cinnamon Bark (Cinnamomum burmannii) and Kaffir Lime Peel (Citrus Hystrix) against the Aedes aegypti mosquito. The method used in this research uses experimental methods. This research was conducted in April - November 2022. This research used two formulations, namely cinnamon bark and kaffir lime peel (FI) formulations which were compared with formulation preparations in the form of a base without active substances (FII). The tests carried out were physical quality tests and repellent tests on the Aedes aegypti mosquito. The research results show that based on physical quality tests, it is known that FI has a distinctive odor, slightly yellowish white color and a thick shape. Meanwhile, FII has the distinctive smell of patchouli oil, milky white color and thick shape. In the homogeneity test on FI and FII it was found to be homogeneous and fulfilled the requirements. In the adhesion and spreadability tests on FI and FII it was found that they met the requirements. In the pH test, the pH of FI and FII has a pH value of 7 and meets the requirements. In the repellent test using arm-in-cage with 3 replications using 20 Aedes aegypti mosquitoes. The formulas tested were FI and FII and observations made were by recording the number of mosquitoes that landed after using the repellent for 15, 30, 60, 120, 240 and 360 minutes. The research results showed that in the 15th minute the protection power was 88.3%, in the 30th minute the protection power was 88.3%, in the 60th minute the protection power was 72.3%, in the 120th minute the protection power was 67, 1%, in the 240th minute the protection power was 51.5%, and in the 360th minute the protection power was 47.7%. Based on the research results, it can be concluded that the essential oil formulation of cinnamon bark and Kaffir lime peel is efficacious as a repellent.